A new tetraradial olivooid (Medusozoa) from the lower Cambrian (Stage 2) Yanjiahe Formation, South China. (May 2020) - Guo, Junfeng; Han, Jian; Van Iten, Heyo; Song, Zuchen; Qiang, Yaqin; Wang, Wenzhe; Zhang, Zhifei; Li, Guoxiang; Sun, Yifei; Sun, Jie
Abstract: Octapyrgites elongatus n. gen. n. sp., a relatively rare, tetraradial olivooid (Cnidaria, Medusozoa), is described from Bed 5 of the Yanjiahe Formation (Cambrian Stage 2) near Yichang, China. Although similar to Olivooides and Quadrapyrgites from the Fortunian Stage in consisting of a partially corrugated (longitudinal) periderm with a quadrate (transverse) apical portion and V-shaped apertural lobes, O . elongatus is substantially larger than other olivooids. The elongate apical region of O . elongatus is similar to four-sided Anaconularia anomala (Barrande, 1867 ), though with a flat tip that may have been an adaption for a sessile mode of life. As in other olivooids, embryonic development in O . elongatus may have been direct. Last, the paucity of olivooids and the absence of pentaradial cnidarians and carinachitids in Cambrian Stage 2 indicate a marked decline in the disparity of cnidarians near the Fortunian–Cambrian Age 2 boundary, when by contrast bilaterians underwent rapid diversification. UUID: http://zoobank.org/60acc2f9-44f8-4a97-9449-960ad76f8fff